Value chain and multi-crop baseline of the Transforming Agrifood Systems in West and Central Africa Initiative (TAFS-WCA): A case study of Nigeria - Arouna, A.; Yergo, W.G.; Aboudou, R.; Ouedraogo, M.; Abdoulaye, T. (Africa Rice Center, 2023)
This report presents the baseline survey of the Transforming Agrifood Systems in West and Central Africa (TAFS-WCA) initiative in Nigeria. Three regions of Nigeria were surveyed. Data were collected with smart tablets using the CSPro application. A total of 1200 actors in agricultural production and value chain were surveyed during the baseline data collection in in Rwanda. These are mainly rice, maize, soybean, beans, cassava, sweet potato, banana, African vegetables, inputs dealers, traders, processors and service providers. All data analyses were carried out with the STATA 16 software. Among the population of producers, 16.33% (196) are rice producers, 8.25% (99) are maize producers, 8.42% (101) are soybean producers, 8.83% (106) are bean producers, 8.58% (103) are yams producers, 8.00% (96) are cassava producers, 8.67% (104) are sweet potato producers, 8.25% (99) are banana producers, 8.33% (100) are African vegetables producers, 0.08% (1) are inputs dealer, 15.33% (184) are traders, 0.33% (4) are processors and 0.58% (7) are service providers. The average age of rice farmers is 40 years old and ranges from 15 to 80 years old, and their mean household size is 7 people. About 74% of actors are male and 93% are married. In addition, 87% of the respondents have received formal education and 82% have crop production as their main activity. Moreover, 97 % of producers grow crops during the rainy season, 2.29% during both seasons while 0.49% in dry season. It should also be noted that in the face of climate change, less than 30% and 22% of producers have access to forecasts of extreme events (drought, flood, strong wind, etc.) and information on seasonal forecasts (weather for the following 2-3 months) respectively. In relation to food security and the poverty index, preliminary results show that the vast majority of farmers’ households have an acceptable level of dietary diversity, meal frequency and nutritional importance of the food groups consumed; and the poverty index of the population is 49%.